Manual and automated aeration strategies during storage of sunflower grains in silos - FERREIRA JUNIOR, Weder Nunes; RESENDE, Osvaldo; SOUSA, Kelly Aparecida de; COSTA, Lílian Moreira; ALMEIDA, Adrielle Borges de; OLIVEIRA, Daniel Emanuel Cabral de; QUIRINO, José Ronaldo (Food Science and Technology, 2025)
The objective of this study was to identify the influence of manual and automated aeration strategies guided by thermometry systems with thermocouples and digital sensors, respectively, on the quality of sunflower grains stored at different heights in a metal silo. The experiment was conducted in a storage unit in two vertical metal silos. Aeration in these silos was manually coordinated in the silo containing thermocouples and automated in the silo with a digital thermometry system. In addition to the grain mass temperature data, the quality of the sunflower grains was monitored for 90 days of storage at three heights in the silo (upper, middle, and lower thirds). The aeration strategies influenced the temperature of the grain mass and, consequently, the quality of the stored product, especially its moisture content. No influence of aeration strategies was identified for protein content, oil content, and iodine content of the oil of the stored sunflower grains. Automation of aeration contributes to making use of better climatic conditions to carry out the process, compared with the manual system used. The aeration strategies adopted (cooling and conservation) were efficient in reducing grain mass temperature in the automated process. The silo with automated aeration showed better conservation of the quality of the stored sunflower grains. The silo with manually controlled aeration showed an 11.55% reduction in grain moisture content. Grains stored in the middle third of the silo tend to have better quality.